Determinan Pendapatan Nasional dan Rekomendasi Kebijakan - Indah Fadilla, Meita; Nurhayati, Nurhayati (Universitas Islam Nahdlatul Ulama Jepara, 2024)
National income is a measurement tool that includes the total value of final output from all productivity results produced in a country over a certain period. It is used to measure the rate of growth of the national economy and determine appropriate policies to encourage economic stimulus. National income provides an overview that can help identify economic structures that need optimization. The purpose of this study was to analyze the effect of final consumption expenditure, gross savings, gross capital formation, population growth rate, and inflation on national income in Indonesia. This study uses the Ordinary Least Square (OLS) analysis method with time series data on each variable from 1990 to 2022. The results showed that final consumption expenditure, gross savings, and gross capital formation had a significant positive effect on national income. Meanwhile, inflation has a positive but insignificant effect, and the population growth rate has a negative but also insignificant effect on national income. The effect of several independent variables on the dependent variable is 91,2%, while 8,8% is influenced by other variables not included in this research model.